2002
DOI: 10.3102/01623737024002113
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituting Schools: “Testing” the “Theory of Action”

Abstract: This article identifies key elements of the “theory of action” embodied in reconstitution reforms and examines them in light of findings acquired from a two-year study that documents what happened when a particular rendition of reconstitution was enacted and implemented. The evidence from this study suggests that the “theory of action” embedded in reconstitution reforms may be seriously, if not fatally flawed. On every critical count, the dominant patterns of implementation ran counter to the major premises (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(96 citation statements)
references
References 19 publications
4
91
0
1
Order By: Relevance
“…4 The literatures on desegregation and peer effects also investigate the effect of shifting students from one school to another. 5 All of these policies differ from school closings in that they do not include the mobility of teachers that is typically generated 1 A related literature that explores the effects of school turnarounds and reconstitutions (i.e., replacing school staff without shifting students to other schools) finds mixed results for student outcomes (Gill et al, 2007;Hess, 2003;Brady, 2003;Malen et al, 2002).…”
Section: Literature Reviewmentioning
confidence: 97%
“…4 The literatures on desegregation and peer effects also investigate the effect of shifting students from one school to another. 5 All of these policies differ from school closings in that they do not include the mobility of teachers that is typically generated 1 A related literature that explores the effects of school turnarounds and reconstitutions (i.e., replacing school staff without shifting students to other schools) finds mixed results for student outcomes (Gill et al, 2007;Hess, 2003;Brady, 2003;Malen et al, 2002).…”
Section: Literature Reviewmentioning
confidence: 97%
“…Research on test-based accountability and principals' work has consistently found that principals play a central role by redirecting time, materials, personnel, and professional development toward improving student achievement on high-stakes assessments (Anagnostopoulos & Rutledge, 2007;Booher-Jennings, 2006;Diamond & Spillane, 2004;Firestone, Monfils et al, 2004;Ladd & Zelli, 2002;Lemons, Luschei, & Siskin, 2003;Malen, Croninger, Muncey, & Redmond-Jones, 2002;Mintrop, 2004). Researchers have found that principals narrow curricular and instructional expectations, redirect instructional time to high-stakes subjects such as reading and mathematics, and increase before-and-after-school activities geared toward improving students' academic achievement (Anagnostopoulos & Rutledge, 2007;Booher-Jennings, 2006;Ladd & Zelli, 2002).…”
Section: Test-based Accountability and Principals' Workmentioning
confidence: 96%
“…It is a public threat as scores are publicized in newspapers and websites, giving parents and other stakeholders quantifiable information that affects their choices, involvement, and expectations of a school (Cobb & Rallis, 2008). It is a workplace threat as state and district administrators use students' test scores as measures of school, principal and teacher performance, closing schools and letting principals go if their schools have not met set benchmarks (Malen et al, 2002;Mintrop, 2004). All of these are attempts to alter the nature of work in schools by encroaching on the instructional activities of administrators and teachers.…”
Section: Jurisdictional Encroachmentmentioning
confidence: 99%
“…In later work, Schneider and Ingram (1990;1997) and McDonnell (2004) added the category of "hortatory" policy, which depends upon generating information and making it public. Policy makers' choices among available policy instruments reflect their assumptions about what causes the problems they are trying to solve, and also about the causal chains that will enable policies to solve or ameliorate the problems (Malen, Croninger, Muncey, & Redmond-Jones, 2002;McDonnell & Elmore, 1987;McDonnell, 2004;Mintrop & Sunderman, 2009). Policies also have symbolic dimensions, in that they express an official commitment to a particular goal, or a particular way of understanding a problem (Gusfield, 1981).…”
Section: Policy Instrumentsmentioning
confidence: 99%